Eficácia de produtos químicos no controle do fungo manchador botryodiplodia theobromae em madeira de hevea brasiliensis - Coneglian, Ademilson; Severo, Elias Taylor Durgante [UNESP] (EIA Energy in Agriculture, 2014)
In Brazil, the exploration and use of the Hevea brasiliensis Mull Arg. wood at the end of the latex production cycle from 30 to 35 years, is practically unknown. However, one of the most significant problems with its use relates to the high susceptibility of this species wood to the fungus Botryodiplodia theobromae attack, especially during the primary wood processing phase. The present study evaluated the efficacy of four chemicals to control juvenile and adult Hevea brasiliensis wood from the attack of the fungus stainer Botryodiplodia theobromae following the ASTM 4445 (2003) standard. The results showed that the active ingredients separately tested and evaluated in the laboratory; (Quinolinolato Copper - 8 and Carbendazim (T1); Tribromofenol 2-4-6 (T2); Extract-Based Vegetable Tannin (T3); Carbendazim and Prochloraz (T4)) do not totally prevent the contamination of Botryodiplodia theobromae in 5% level of significance

No Brasil a exploração e a utilização da madeira de Hevea brasiliensis, no final do ciclo produtivo de látex de 30 a 35 anos, é praticamente desconhecida. Contudo, um dos problemas mais sérios relacionados à sua utilização diz respeito à alta susceptilibilidade da madeira ao ataque de fungos manchadores, principalmente pelo fungo manchador Botryodiplodia theobromae, têm sido apontadas como causa da baixa aceitação de madeira serrada no estado de São Paulo. No presente trabalho avaliou-se a eficácia de quatro produtos químicos no controle de manchamento dos lenhos juvenil e adulto da madeira de Hevea brasiliensis contra o ataque do fungo manchador Botryodiplodia theobromae em laboratório seguindo a norma ASTM 4445. Os resultados mostraram que os ingredientes ativos testados e avaliados isoladamente em laboratório o quinolinolato de cobre – 8 e carbendazim (T1) a 4,0%; 2-4-6 tribromofenol (T2) a 4,0%; extrato vegetal a base de tanino (T3) a 6,0% e carbendazim e prochloraz (T4) a 1%, não previnem na totalidade a contaminação do fungo manchador Botryodiplodia theobromae nos lenhos juvenil e adulto da madeira de Hevea brasiliensis ao nível de 5% de significância, que por sua vez os tratamentos T1, T2, T3 e T4 superaram a testemunha.
Efficacy of chemical control of botryodiplodia theobromae attack to hevea brasiliensis wood products
Keywords: Juvenile and Mature Wood; Hevea brasiliensis; Botryodiplodia theobromae; Chemical preservatives.; Juvenile and Mature Wood; Hevea brasiliensis; Botryodiplodia theobromae; Chemical preservatives.